Приключения Карандаша и Самоделкина: сказоч. повести / Ю. Дружков - Дружков Юрий (Библиотека Солнышкина, 1997)
Экземпляры: (20170529) / Инвентарный номер: 33657 / Цена: 24.80 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д 76 / ББК: 84(2Рос=Рус)6